A critical analysis of a reliability study of ball grid array electronic components submitted to thermal aging and board-level drop test. (October 2021) - Monlevade, Eduardo Franco de; Cardoso, Idélcio Alexandre Palheta; Souza, Gilberto Francisco Martha de
Highlights: The results of first failures in a board-level drop test are analyzed focusing on switching failure mechanisms. Different failure mechanisms are correlated to inflexions in the failure probability curves. Explanations given by other authors to the results found are critically evaluated. Abstract: In the present study, a previous solder joint reliability study is revisited. The results of drop tests conducted on Ball Grid Array (BGA) electronic components mounted onto printed circuit boards with copper terminals coated with Organic Solder Preserver (OSP) submitted to aging heat treatments are studied, focusing on the possibility of identifying switches in failure mechanisms with increasing time-to-failure. The results are discussed based on microstructural characteristics of lead-free solders and its influence on crack propagation. The failure mechanisms encountered are discussed, as well as the explanations given by other authors in the literature for the seemingly contradictory results obtained. The wide range of competing failure mechanisms activated during drop tests and microstructural features such as morphology of phases encountered and the presence of voids contribute significantly to the dispersion of the data, and should be taken under consideration whenever reliability studies based on drop tests are performed. Although this feature is not usually considered in reliability tests, Weibull analyses are efficient to identify the occurrence of competing or switching mechanisms, and even at what point of the life expectance each one is likely to take over.